SIKAP MEREK, PERCEIVED QUALITY, DAN PRESTISE MEREK TERHADAP ADVOKASI MEREK MELALUI KEPERCAYAAN MEREK PADA KLINIK GIGI ORTODONTI DI JAKARTA - Vinna Lovely Hendika; Sri Vandayuli Riorini (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2014)
The background of this research was to trust a brand; a consumer will have on brand attitude. Brandattitude is an overall evaluation of the consumer to the brand. Of a positive assessment of a brand canlead customers into believing the service that is given so that the company believes this attitude that ledto patient satisfaction and intend to go back again using the same service. Brand Trust is the impact ofBrand Advocacy, Brand Attitude, Brand Prestige and Perceived Quality. When a trusted brand that hasprestige in this case may lead consumers to buy products or services feel it again and then the attitudeof loyalty was formed. With the level of consumer loyalty can give a positive attitude toward the brand,which consumers can trust and be advocates in defending the brand.The objectives of this research were to analyze the effect of brand attitude, perceived quality andbrand prestige of the brand trust. And analyze the effect of brand attitude, perceived quality andbrand prestige on brand advocacy.The design of this research applies hypothesis Testing aimed to examine the relationship between thevariables studied. Sample as many as 170 patients were examined you’ve ever come to a particularorthodontic dental clinic. The sampling technique used was purposive sampling. Model used is basedon research criteria.Data analysis used in this research was collected by questionnaire technique, namely by providing awritten statement to the respondent. Furthermore, the respondents to respond to the statement given.Questionnaires were administered are closed and where the answer is already available. In this studybefore distributing questionnaires to test the validity and reliability of the research instrument in orderto obtain a valid measurement tool and reliable.The result of this research concludes that Brand Trust is the impact of Brand Advocacy, Brand Attitude,brand prestige and Perceived Quality. When satisfied customers or patients of a product willautomatically arise WOM (Word of Mouth). WOM provide significant assessment of the customerratings. Action in Brand Advocacy WOM is associated with customers who already believe or trust thecompany’s brand because customers feel satisfied.Keywords :Brand Attitude, Perceived Quality, Brand Prestige, Brand Advocacy, Brand Trust, Word ofMouth